What role can videogames play in the COVID-19 pandemic? [version 1; peer review: 2 approved] - Rachel Kowert; Hannah R. Marston (Emerald Publishing, 2020)
Video games are often thought of as trite activities for younger generations. However, research in game studies over the last few decades have revealed that games can be valuable tools for growth and connection, particularly among older generations. Exploring the ways digital games can be used as tools for connection has gained increased attention in recent months with global quarantines as a result of COVID-19. This article reviews the research that has examined the utility of digital games for older adults, focusing specifically on the ways in which games can be tools for social connectedness and psychological healing for older adults and intergenerationally. Special focus will be placed on the role games can play for post-traumatic stress among first responders.